2009
DOI: 10.1055/s-0028-1103452
|View full text |Cite
|
Sign up to set email alerts
|

Endocytoscopy can identify dysplasia in aberrant crypt foci of the colorectum: a prospective in vivo study

Abstract: Endocytoscopy provides real-time histological images in vivo, with clear visualization of cellular details and features of dysplasia in colorectal ACF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Subsequently, several investigators have confirmed our proposal of the ACF-adenoma-carcinoma sequence through demonstrating a close relationship between ACF and adenomas or cancers in terms of number, size, and pathologic features (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 71%
“…Subsequently, several investigators have confirmed our proposal of the ACF-adenoma-carcinoma sequence through demonstrating a close relationship between ACF and adenomas or cancers in terms of number, size, and pathologic features (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 71%
“…Different studies suggest the potential of endocytoscopy for the in vivo evaluation of duodenal mucosa in celiac disease [21] . Furthermore, endocytoscopy was able to detect tissue abnormalities in normal mucosa surrounding colorectal cancer and to identify neoplasia in aberrant crypt foci [22] . Additionally, endocytoscopy was shown to distinguish neoplastic from non-neoplastic lesions, and also to differentiate invasive colon cancer from adenoma [23,24] .…”
mentioning
confidence: 99%
“…Recently, endocytoscopy has been established as a useful tool to examine mucosal surfaces [20][21][22][23] . Different studies suggest the potential of endocytoscopy for the in vivo evaluation of duodenal mucosa in celiac disease [21] .…”
mentioning
confidence: 99%
“…Multiple-step procedures including extensive washing followed by methylene blue staining are time consuming and considered as the disadvantage of ECS in the cytological/ architectural observation for GI neoplasms. 16 However, extensive washing is not necessary to observe amebic trophozoites because they are usually found in the mucus on the surface of aphthae. In other words, excessive washing may rather reduce the possibility of finding residual trophozoites.…”
Section: Discussionmentioning
confidence: 99%